A survey of Dryinidae (Hymenoptera, Chrysidoidea) from Caxiuanã, Amazon Basin, with three new taxa and keys to genera and species - Coelho, Beatriz W.; Aguiar, Alexandre P.; Engel, Michael S. (Zootaxa, 2011)
The dryinid wasp fauna of Caxiuanã National Forest, Pará, Brazil is summarized. Seventeen species, three of which are new, in six genera and three subfamilies have been found: Anteoninae: Anteon panamense Olmi, A. chiriquense (Cameron), A. noyesi Olmi, Deinodryinus bicolor (Olmi et Currado), D. bilobus Fenton, D. caxiuana sp. nov.; Dryininae: Dryinus argentinus Olmi, D. striatus (Fenton), D. snellingi Olmi, D. ruficeps Cameron, D. multicarinatus sp. nov., D. hamulus sp. nov.; Gonatopodinae: Gonatopus campbelli Olmi, G. neotropicus (Olmi), G. testaceus Cameron, Neodryinus incaicus Olmi, and Trichogonatopus neotropicus Olmi. Gonatopus neotropicus and N. incaicus are newly recorded from Brazil. The new species are described and illustrated. Keys to genera and species are provided.